KURASH SPORTINING O`RNI: KURASH SPORTINING O`RNI - Jumadurdiyev, Bahodir (Физическое воспитание, спорт и здоровье, 2024)
wrestling, values, history of sports, Ministry of Tourism and Sports, ―Umid Nihollari‖, ―Barkamol Avlod‖, ―Universiada‖, youth development